2-Amino-4,6-dimethoxypyrimidin-1-ium p-toluenesulfonate - Gomathi, Sundaramoorthy (International Union of Crystallography, 2011)
In the title salt, C(6)H(10)N(3)O(2) (+)·C(7)H(7)O(3)S(−), the 2-amino-4,6-dimethoxypyrimidinium cation interacts with the sulfonate group of the p-toluenesulfonate anion via a pair of N—H⋯O hydrogen bonds, forming a cyclic hydrogen-bonded R (2) (2)(8) motif, which in the crystal is linked by further intemolecular N—H⋯O hydrogen bonds, forming supramolecular chains along the c axis. Furthermore, neighboring chains are interlinked via weak C—H⋯O hydrogen bonds and C—H⋯π interactions, forming layers.